Eksplorasi Jamur Alkalotoleran dari Desa Sukolilo Barat, Kecamatan Labang, Kabupaten Bangkalan, Madura, Jawa Timur - Lusiana, Helga; Rukmi, MG Isworo; Raharjo, Budi (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2014)
Mold exploration from limestone hills West Sukolilo village, District Labang, Bangkalan, Madura, East Java, conducted to found the alkalotolerant mold isolates and investigate their amylolytic, proteolytic, and cellulolytic activity. Mold isolation were done using spread plate and dilution method on PDA and CMA at pH 8.0, 9.0, and 10.0. Twenty-seven mold isolates have been found consist of four genus i.e. Aspergillus, Fusarium, Curvularia, and Trichoderma. The result of amylolytic test showed Trichoderma longibrachiatum (IMD-26) have the highest activity at pH 8, while Fusarium sp 2 (IMD-24) showed the highest activity at pH 9. Aspergillus flavus (IMD-7) showed highest proteolytic activity at pH 8, while Hyphomycete (IMD-27) showed the highest activity at pH 9. The highest cellulolytic activity at pH 8 showed by Trichoderma harzianum (IMD-25) and pH 9 by Fusarium sporotrichoides (IMD-20). Keyword : alkalotoleran mold, amylolytic, proteolytic, cellulolytic.